Avaliação do desenvolvimento do Camurim Centropomus parallellus (Poey, 1860) em água doce, submetido á alimentação artificial - Cavalheiro, José Marcelino de Oliveira (Universidade Federal de São Carlos, 2000)
Experiments with snook cultivation, Centropomus parallelus, aiming at increasing the continental pisciculture, mainly in northeast Brazil, were carried out in two stages. The first one was carried out at the laboratory of the Federal University of Paraíba, aiming to determine the optimum diet for increasing snook weight, in a 3 X 3 factorial treatment using feeds containing 35, 40, and 45% of crude protein and 3000, 3100, and 3200 kcal energy. The nine diets used here were prepared from ingredients obtained in the localities of the present study. They were added to 45 aquaria (50 L capacity each) with alevins obtained from spawning performed at a laboratory of the federal University of Santa Catarina, southern region of Brazil, presenting an initial average weight of 1.70g and stocked in a density ca 20 fish/m2, during a period of nine weeks. The best performance concerning the snook protein requirement was obtained by using 45% crude protein diet and with intermediary energy levels of 3100 kcal. On the second stage, fieldworks were performed in the municipalities of São Bento and Bananeiras, located in the mesoregion of sertão (microregion of Catolé do Rocha ) and mesoregion of agreste (microregion of Brejo ) in Paraíba State, respectively, where development of snooks obtained from spawning and fed with the best feed determined on the first stage, was estimated. The same management procedures were utilized in both localities. In São Bento, two aquaria (270m2 each) belonging to the fish farming Fazenda PROSAL Aquacultura S/A were utilized, from 26th May/1998 to 26th May/1999. In Bananeiras, two tanks (100m2 each) belonging to the Pisciculture Station of IBAMA (Insitute for the Environment and Natural Resources) were utilized, from 11th June/1998 to 11th June/1999. Both places were selected because they have the greatest number of pisicultures in Paraíba State. High fluctuations of limnological variables, mainly nutrients (ammonium, nitrite, and nitrate) occurred during the experiments acting upon snook, which showed to be a rough species. A positive and significant correlation (p (< ou =) 0.05) was obtained between zooplancton belonging to Other Organisms group (ostracods, chironomids, oligochaetes, insects larvae, etc) and the Weight Increase Rate. However, among the natural food occurring in the cultivation ponds (in São Bento) cladocerans were the snook favourite food, whereas in the tanks (in Bananeiras) Other Organisms group was its favourite food. Through the best adjusted values index (r2) obtained from several growth mathematical equations used here, the polynomial model showed to be noteworthy, despite significant differences between the snook groups development from the aquaria and from the tanks was not obtained.
Evaluation of the development of snook, Centropomus parallelus (POEY, 1860), fed artificially in freshwater, in Paraíba state, Brazil
Keywords: Peixe; Peixe - alimentação; Camurim - robalo; Curva de crescimento; Alimento natural; CIENCIAS BIOLOGICAS::ECOLOGIA